Long (Standing) Digital Divisions: Women's IT Work in Canada - Scott-Dixon, Krista (Atlantis, 2008)
This article explores the concept of "digital divide" as it pertains to women's work in and with IT in Canada. While "digital divide" has some usefulness as an analytical concept for feminist scholars, the complex nature of IT-based work requires a broader and deeper understanding.